2014
DOI: 10.1186/1471-2431-14-187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of home-based counselling on newborn care practices in southern Tanzania one year after implementation: a cluster-randomised controlled trial

Abstract: BackgroundIn Sub-Saharan Africa over one million newborns die annually. We developed a sustainable and scalable home-based counselling intervention for delivery by community volunteers in rural southern Tanzania to improve newborn care practices and survival. Here we report the effect on newborn care practices one year after full implementation.MethodsAll 132 wards in the 6-district study area were randomised to intervention or comparison groups. Starting in 2010, in intervention areas trained volunteers made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 25 publications
(56 reference statements)
1
52
0
Order By: Relevance
“…The breastfeeding education studies were con4ducted in a wide range of countries spanning four continents, i.e., twelve studies in Africa; one in Egypt [22]; two in Ghana [23,57]; two in Uganda [37,63]; one in Nigeria [38]; two in Tanzania [44,73]; two in Kenya [56,70]; one in South Africa [49]; one study in three countries of Africa [92]; Burkina Faso, Uganda and South Africa. Twenty-four studies were conducted in Asia; six in Bangladesh [26,27,51,53,89,95]; three in India [29,65,67]; one in Nepal [32]; two in Iran [39,75]; one in China [42]; one in Jordan [54]; one in Thailand [58]; one in Pakistan [83]; one in Malaysia [87]; two in Turkey [24,33]; one in Philippines [21].…”
Section: Study Selectionmentioning
confidence: 99%
“…The breastfeeding education studies were con4ducted in a wide range of countries spanning four continents, i.e., twelve studies in Africa; one in Egypt [22]; two in Ghana [23,57]; two in Uganda [37,63]; one in Nigeria [38]; two in Tanzania [44,73]; two in Kenya [56,70]; one in South Africa [49]; one study in three countries of Africa [92]; Burkina Faso, Uganda and South Africa. Twenty-four studies were conducted in Asia; six in Bangladesh [26,27,51,53,89,95]; three in India [29,65,67]; one in Nepal [32]; two in Iran [39,75]; one in China [42]; one in Jordan [54]; one in Thailand [58]; one in Pakistan [83]; one in Malaysia [87]; two in Turkey [24,33]; one in Philippines [21].…”
Section: Study Selectionmentioning
confidence: 99%
“…Five studies described multi-modal interventions within a health care facility, either for general quality improvement [58][59][60] [63][64][65] and three studies of healthcare facility-based interventions [66][67][68]. One study evaluated a community and facility-based intervention [69].…”
Section: Determinants Identified In Intervention Studiesmentioning
confidence: 99%
“…One study evaluated a community and facility-based intervention [69]. The most commonly targeted determinant was knowledge of the mother or birth attendant, with four interventions aiming to improve knowledge through increased use of maternal and newborn services [69], home-based maternal counselling by community volunteers [63], improved quality of facilitybased maternal counselling through use of visual job-aids [68], or facility-based training of care providers on essential newborn care practices [67]. Two studies highlight the critical importance of participatory approaches, meaning the active involvement of women, families, and community members in effecting behaviour change, in contrast to models based purely on education [64,65].…”
Section: Determinants Identified In Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that community-based health systems, particularly those involving CHWs, have led to improved access to maternal healthcare services [1315], modern contraception [16, 17], and neonatal care among the poor [1822]. However, recently only few studies have investigated the impact of interventions made by CHWs on childhood illness in sub-Saharan Africa, using randomized controlled trials (RCTs) [2326].…”
Section: Introductionmentioning
confidence: 99%